Modeling one-handed grip strangulation: Intentionality of the gesture and age influence. (November 2021) - Gagnon, C.; Godio-Raboutet, Y.; Piercecchi, M.D.; Thollon, L.
Highlights: Injuries are different for this study that include the environment of each the anatomical part. The average grip force does not seems enough to fracture the bony part of the neck. There is an age influence in the fracture pattern. Abstract: Strangulation is a violent act which can be lethal and is often studied in forensic context. The neck includes several anatomical elements that can evolve with aging. We therefore created a numerical human neck model including the main anatomical elements and simulated one-handed grip strangulation cases. In addition, we created 3 models each representing age groups: 20–30 years old, 30–50 years old and over 50 years old. The main changes between the different age groups are the ossification of the cartilages and the muscles mechanical properties. Several initial and boundary conditions have been tested to perform a realistic simulation of one-handed grip strangulation. Stress analysis and fracture observation were compared with the grip strength of an average man, 552 N, to look at the intentionality of the gesture. In each age group, the results show no model fracture for a force of 552 N. It is necessary to reach a minimum of 1406 N before observing a first fracture on the hyoid bone. However, it is possible to get stresses on the hyoid bone and on the thyroid cartilage way before 552 N. It thus appears that the force created by one-handed grip strangulation is not sufficient to cause fractures of the bony elements of the neck, but it remains sufficient to compress the larynx and at least reduce airflow.